Pengembangan Buku Bujang Dare Anti Perundungan Untuk Siswa Sekolah Dasar Di Kota Pontianak Sebagai Edukasi Bahaya Perundungan - Dyoty Auliya Vilda Ghasya; Kartono Kartono; Nanny Safrianty; Bayu Prasodjo; Ahmad Yani T (JPDI (Jurnal Pendidikan Dasar Indonesia), 2025)
This research aims to develop a book aimed at elementary school students as education about the dangers related to bullying. This book contains educational content about bullying in the school environment. The research method used is development research. The data needed in research on the development of the book "Bujang Dare Anti-Bullying" for elementary school students in the city of Pontianak as education on the dangers of bullying consists of two types of data, namely qualitative data and quantitative data. The research data collection instruments used include; (1) checklist or instrument validation questionnaire sheet at the product validation stage, (2) questionnaire sheet at the product trial stage, and (3) questionnaire sheet at the usage trial stage. The material validation results obtained a score of 86.76 with a very valid category; The language validation results obtained a score of 85 with a very valid category; The design validation results obtained a score of 88.17 with a very valid category. Meanwhile, the results of student responses regarding the practicality of using the book product "Bujang Dare Anti-Bullying" for elementary school students in the Pontianak obtained a practicality score of 96.55 with very practical criteria. Meanwhile, the results of the teacher's response obtained a practicality score of 94.60 with very practical criteria. In conclusion, the Bujang Dare Anti-Bullying book not only educates students about the dangers of bullying, but also strengthens local values and morals, so it is suitable to be used as open material to create a safer and child-friendly school environment.